Gliomatosis Peritonei associated with Ovarian Immature Teratoma - A rare entity - Maharjan, Daisy; Gaire, Deepshikha; Dhakal, Sheela; Tiwari, Sansar Babu (Nepal Journal of Health Sciences, 2022)
Gliomatosis peritonei is a rare entity associated with ovarian teratoma, both mature and immature. We present a case of a 24-year-old female diagnosed with immature ovarian teratoma, grade 2 on histopathological examination. The presence of mature glial tissue on the omentum tissue established the diagnosis of gliomatosis peritonei. It is a harmless condition with a favorable prognosis. However, regular follow-up is required as it is associated with the risk of recurrence and malignant transformation. Adequate sampling and examination of multiple biopsies for the presence of an immature neural element is important to rule out metastatic involvement.